Extracellular Optogenetics at the Interface of Synthetic Biology and Materials Science - Månsson, Lisa K.; Pitenis, Angela A.; Wilson, Maxwell Z. (Frontiers in Bioengineering and Biotechnology, 2022)
We review fundamental mechanisms and applications of OptoGels: hydrogels with light-programmable properties endowed by photoswitchable proteins ("optoproteins") found in nature. Light, as the primary source of energy on earth, has driven evolution to develop highly-tuned functionalities, such as phototropism and circadian entrainment. These functions are mediated through a growing family of optoproteins that respond to the entire visible spectrum ranging from ultraviolet to infrared by changing their structure to transmit signals inside of cells. In a recent series of articles, engineers and biochemists have incorporated optoproteins into a variety of extracellular systems, endowing them with photocontrollability. While other routes exist for dynamically controlling material properties, light-sensitive proteins have several distinct advantages, including precise spatiotemporal control, reversibility, substrate selectivity, as well as biodegradability and biocompatibility. Available conjugation chemistries endow OptoGels with a combinatorially large design space determined by the set of optoproteins and polymer networks. These combinations result in a variety of tunable material properties. Despite their potential, relatively little of the OptoGel design space has been explored. Here, we aim to summarize innovations in this emerging field and highlight potential future applications of these next generation materials. OptoGels show great promise in applications ranging from mechanobiology, to 3D cell and organoid engineering, and programmable cell eluting materials.